Thrombolytic Therapy for Acute Myocardial Infarction: Lessons to Be Learned - Sherry, Sol (1991)
Trials of thrombolytic therapy have taught us that 1) lysis of hemostatic plugs, not fibrinogenolysis, is the major cause of bleeding complications; 2) as currently reported, patency rates 90 minutes after the onset of therapy are both meaningless and misleading as surrogate end-points for either myocardial salvage or reduced mortality; 3) extensive restoration of myocardial function requires much earlier administration of thrombolytic therapy than is currently the practice; 4) reduced mortality can be demonstrated well after the period in which myocardial salvage can be shown; and 5) drug development based on fibrin specificity is probably an obsolete concept, because therapy with a fibrin-specific agent such as recombinant tissue-type plasminogen activator does not enhance safety and is associated with a high degree of rethrombosis. (Texas Heart Institute Journal 1991;18:103-9)